2019
DOI: 10.1016/j.jallcom.2018.10.360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cation disorder on magnetic properties of new double perovskites La2Ni Co1-MnO6 (x = 0.2–0.8)

Abstract: The effect of cation disorder on magnetic properties of new double perovskites La 2 Ni x Co 1-x MnO 6 (x = 0.2-0.8),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…33 Recently, the magnetic dilution effect in La 2 Co 1−x Mg x MnO 6 revealed similar suppression of hightemperature ferromagnetism. 34 However, the substitution of Co by Ni results in an upward shift of the high temperature T C in La 2 Ni x Co 1−x MnO 6 as per expectation since La 2 MnNiO 6 exhibits magnetic ordering at 280 K. 35 Recently, substitution of Mn by Ru in La 2 Mn 1−x Ru x CoO 6 (x = 0, 0.1, 0.2, 0.3, 0.5, 0.75, 1.0) is reported to exhibit structural transition from disordered orthorhombic (0 ≤ x ≤ 0.3) to ordered monoclinic structure for 0.5 ≤ x ≤ 1 and the ferromagnetic T C gradually decreases with the increase in Ru up to x = 0.75 eventually switching to an antiferromagnetic phase for x = 1. 36 The subtle role of structural effect, cationic disordering, and valence ratio Mn 3+ /Mn 4+ and Co 3+ /Co 2+ as well as the presence of other cations in the B-site is yet to be understood properly.…”
Section: ■ Introductionmentioning
confidence: 86%
“…33 Recently, the magnetic dilution effect in La 2 Co 1−x Mg x MnO 6 revealed similar suppression of hightemperature ferromagnetism. 34 However, the substitution of Co by Ni results in an upward shift of the high temperature T C in La 2 Ni x Co 1−x MnO 6 as per expectation since La 2 MnNiO 6 exhibits magnetic ordering at 280 K. 35 Recently, substitution of Mn by Ru in La 2 Mn 1−x Ru x CoO 6 (x = 0, 0.1, 0.2, 0.3, 0.5, 0.75, 1.0) is reported to exhibit structural transition from disordered orthorhombic (0 ≤ x ≤ 0.3) to ordered monoclinic structure for 0.5 ≤ x ≤ 1 and the ferromagnetic T C gradually decreases with the increase in Ru up to x = 0.75 eventually switching to an antiferromagnetic phase for x = 1. 36 The subtle role of structural effect, cationic disordering, and valence ratio Mn 3+ /Mn 4+ and Co 3+ /Co 2+ as well as the presence of other cations in the B-site is yet to be understood properly.…”
Section: ■ Introductionmentioning
confidence: 86%
“…[11,12] Harbi et al have reported effect of cation disorder and study the structural and magnetic properties of "Co" doped LNMO and confirmed that it has monoclinic structure with space group P21/n. [13] Najar et al have reported optical properties of LNMO with the substitutional doping of lanthanum manganate oxide and confirmed that optical bandgap of the material in varies from the electronic bandgap due to excitonic effects. [14] Sheikh et al have reported the theoretical DFT calculations and experimental work on Sm 2 NiMnO 6 double perovskite which is almost similar kind of materials as of LNMO and show properties for solar applications.…”
Section: Introductionmentioning
confidence: 92%
“…have reported effect of cation disorder and study the structural and magnetic properties of “Co” doped LNMO and confirmed that it has monoclinic structure with space group P21/n. [ 13 ] Najar et al. have reported optical properties of LNMO with the substitutional doping of lanthanum manganate oxide and confirmed that optical bandgap of the material in varies from the electronic bandgap due to excitonic effects.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the ability of a complex oxide to accommodate disorder has been linked to its amorphization resistance. [1][2][3] Further, many functional properties of complex oxides, including conductivity, [4][5][6][7] mechanical properties, 8 energy density, 9 and magnetic properties, 10 are sensitive to the level of cation disorder in the material. Thus, it is of general interest to understand which oxides will readily disorder and which will not.…”
Section: Introductionmentioning
confidence: 99%